Implications of Social Change in the Development of Information and Communication Technology in Asian Countries - Nisa Miftachurohmah; Meisuri Meisuri; Loso Judijanto; Hayu Lusianawati (Westscience Press, 2023)
This research explores the implications of social change in the development of Information and Communication Technology (ICT) within Asian countries through a comprehensive analysis of academic literature. Utilizing a bibliometric approach and thematic analysis, the study examines 980 papers published between 1922 and 2023. The thematic analysis reveals recurring terms, with